Assessment of Organic Matter Influence on the Ecological Integrity of Poyang Lake Using O/E Model and Chemical–Biological Indices over the Past Two Decades - Jindong Wang; Wenjie Huang; Chenglian Feng; Hongyang Wang (Toxics)
Ecological integrity, encompassing physical, chemical, and biological aspects, is crucial for sustaining ecosystem service functions and stability. As the largest freshwater lake in China, the ecological integrity of Poyang Lake has attracted much attention due to the over-exploitation of its water resources in recent years. In this study, several biological and water quality surveys on water ecological conditions were carried out at 11 sampling points of Poyang Lake from 1998 to 2022, and the ecological health of Poyang Lake was evaluated by use of the O/E (Observation/Expectation) model and the chemical–biological index method according to the status of the water quality and the structure of the benthic fauna in the four seasons, respectively. The results showed that the benthic community structure is simple, and the biodiversity is low, which is mainly dominated by Insecta in Arthropoda and Oligochaeta in Oroidea, accounting for 84.3% and 42.4%, respectively; the results of the O/E index evaluated under the threshold of probability of capture ≥ 0.5 showed that the health grade of all sections was sub-healthy or average, which was consistent with the results of the chemical–biological composite index evaluation. The dual evaluation method of the O/E model and chemical–biological composite index adopted in this study integrates more than twenty years of long-time scale data; this method combined with long time scale data has not been studied before, and its advantage is that it can more objectively show the change in the ecological situation of Poyang Lake for many years. The results of the present study could provide a theoretical basis and technical support for the evaluation of lake water environment quality.